Effect of Enterococcus faecium strain 18 on fungi of the genus Candida - Olga A. Pashinina; Tatiana M. Pashkova; Maria V. Sycheva; Lidia P. Popova; Olga L. Kartashova (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Enterococcus spp. which are representatives of the intestinal normal microbiota, play an important role in ensuring colonization resistance of mucous membranes, producing antimicrobial compounds, and therefore are widely used as the basis of probiotic drugs. In the last decade, infections caused by Candida fungi have become a serious clinical problem. In this regard, it is relevant to evaluate the probiotic characteristics of the E. faecium strain 18 and study its antifungal activity.